087 Prognostic value of myocardial contrast echocardiography in heart failure patients. (22nd September 2015) - Anantharam, B; Hayat, S; Hickman, M; Janardhanan, R; Chelliah, R; Senior, R
Abstract : Background: The prevalence of left ventricular (LV) dysfunction and resultant congestive heart failure is increasing. Patients (pts) with this condition are at high risk for cardiac death and usually have significant limitations in their lifestyles. Myocardial viability and ischaemia are predictors of mortality in pts with heart failure (HF). MCE is a relatively new method for the assessment of the myocardial viability and ischaemia at the bedside. However, its prognostic value is unknown in patients with heart failure. Methods: Ninety-two pts (age: 68±9 years, 60% male) with heart failure (LVEF: 35±14) underwent low power intermittent MCE (SonoVue) at rest and 2 min after dipyridamole infusion. A semiquantitative scoring system was used to assess contrast intensity at 15 cardiac cycles after a destructive pulse: 2-homogenous opacification, 1-reduced or heterogeneous opacification, and 0-minimal or absent contrast opacification. Resting and stress perfusion score index (RPSI and SPSI) were calculated by averaging the scores in all 16 segments. RPSI is a measure of myocardial viability (MV). Ischaemic burden was calculated by deducting RPSI from SPSI. Resting and hyperaemic myocardial blood flow (MBF) (peak contrast intensity x myocardial blood velocity) was obtained by quantitative method and coronary flow reserve (MBF at stress/MBF at rest) was calculated in the anterior and infero-posterior circulation and averaged for each patient. All pts underwent coronary arteriography. Patients were followed-up for all cause mortality. Results: Of the 92 pts, 44 (48%) pts had coronary artery disease (CAD). There were 28 (30%) deaths during a mean follow-up of . Cox regression analysis showed that gender (p=0.03), age (p=0.03), diabetes mellitus (p=0.02), presence of CAD (p=0.004), Revascularisation (p=0.03), MV (p=0.008), Ischaemic burden (p=<0.001) and CFR (p=0.001) were univariate predictors of mortality. Multivariate analysis showed that diabetes mellitus (p=0.01), presence of CAD (p=0.04), MV (p=0.03), Ischaemic burden (p=0.03) and CFR (p=0.01) were independent predictors of mortality. A CFR≤1.5 predicted mortality of 53% vs 10% (p<0.0001) when CFR >1.5. A significant improvement in global χ 2 value was noted with CFR over clinical variables, coronary angiographic data and myocardial viability and ischaemic burden. Conclusions: Jeopardised myocardium determined by MCE is a powerful predictor of mortality in pts with HF.